(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2020)
Selective chemical reactions create new possibilities for controlled synthesis of compounds with pre-designed properties for further use in medical chemistry, material science and other fields. This is especially useful for such synthetic methodology as [4+2] cycloaddition. Current work is dedicated to study of reactions between N-chiral maleinimides with cyclic dienes based on the pyridoisoindol. Pyrido[2,1-a]isoindol turned out to be the most practical object to study the first example of asymmetric variant of the Diels-Alder reaction involving condensed isoindols. Previously, we established that this heterocyclic system, in contrast to other azino- and azoloisoindols, upon undergoing cycloaddition with non-chiral maleinimides gives only rearranged adducts of the first type. This type of compounds have also interesting stereochemistry: in solid state they have twisted double bond (twist angle 7-10°), while in solution they exist as a mixture of athropodiastereomeres due to the asymmetric Carbon atom and hindered rotation around С–С bond between exocyclic double bond and 2-(α-pyridil)phenyl fragment. Initial expectation was that chiral induction would influence the ratio of corresponding athropodiastereomeres. Calculations show that there are four possible athropodiastereomeres due to the chiral center and sterically hindered chiral axis. In case of non-chiral dienophiles, reaction results in two major diastereomeres (for our purposes marked as A and B) with 70:30 ration and two minor isomers (marked С and D respectively), the latter constituting less than 5% of the total amount. Major and minor isomers are in constant complex equilibrium, controlled via slow rotation of around corresponding С-С bond on one hand (which is the reason for athropodiastereomeres between major forms A and B, shown via NMR spectra at different temperatures), and on the other hand – fast equilibrium due to the 1,5-sigmatropic shift (cause for the minor forms C and D). Target reaction was studied under standard conditions for this rearrangement and under the kinetic control in the inert atmosphere at -80°С using TiCl4 as catalyzer. We therefore show that reaction pathway is similar to our previous examples and results in rearranged adducts of the first type. Ratio of athropodiastereomeres (both major and minor forms) is different from previous examples using non-chiral 2-substituted maleimides. Asymmetric induction spontaneously transfers from influencing the Diels-Alder reaction to influencing synchronic sigmatropic rearrangement, which is the final stage in the formation of the rearranged adduct of the first type in condensed isoindol systems.